The Effect Of Competence, Career Development And Indirect Compensation On Employee Performance With Job Satisfaction As An Intervening Variable At Kontak 157 Financial Services Authority - Butar-Butar, Helena; Efendi , Suryono (Jurnal Ekonomi, 2024)
The Influence of Competence, Career Development and Indirect Compensation on Employee Performance with Job Satisfaction as an Intervening Variable at Contact 157 Financial Services Authority. The method used is descriptive quantitative statistical tool Structural Equation Modeling (SEM). The results of this study conclude that Competence, career development, indirect compensation have a positive and significant effect on Job Satisfaction. Competence and career development have a positive and significant effect on performance. While indirect compensation has a negative and insignificant effect on performance. Job Satisfaction has a positive and significant effect on Performance. Job Satisfaction is able to mediate the effect of Competence, career development, and indirect compensation on Performance.